2020
DOI: 10.3390/su12219200
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between Corporate Social Responsibility Report and the Stock Market

Abstract: This study mainly investigates the relationship between corporate social responsibility (CSR) reporting and the reaction in the stock market. Specifically, we utilize the data from Taiwanese stock market from 2012 to 2017 to examine whether the CSR report disclosed by the listed companies on the Taiwan Stock Exchange and the Taipei Exchange will cause abnormal returns on the short-, mid- or long-term horizon. The empirical results demonstrate that companies which disclose their CSR reports generate higher and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…These results confirm H1, H3, and H4 and are consistent with Johnson and Woodcock, 2019 , Kim and Kim, 2022 , and Oh and Kim (2022) , as they highlight the relevance of Twitch for video game companies. Also agree with Cheung, 2011 , Friede et al, 2015 , Zhang et al, 2018 , Chiu et al, 2020 among others on the existence of a positive influence of sustainability on stock returns, in this case, of video game companies.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…These results confirm H1, H3, and H4 and are consistent with Johnson and Woodcock, 2019 , Kim and Kim, 2022 , and Oh and Kim (2022) , as they highlight the relevance of Twitch for video game companies. Also agree with Cheung, 2011 , Friede et al, 2015 , Zhang et al, 2018 , Chiu et al, 2020 among others on the existence of a positive influence of sustainability on stock returns, in this case, of video game companies.…”
Section: Resultssupporting
confidence: 84%
“…Many studies have demonstrated a positive relationship between sustainability and increased performance ( Ziegler et al, 2007 , Chiu et al, 2020 , Lee and Suh, 2022 ; etc). Friede et al (2015) conducted a meta -analysis of approximately 2200 empirical studies in various areas, accounting, economics, finance, and management, and stated that “the business case for ESG investing is empirically very well founded.” “Roughly 90 % of studies find a nonnegative Environmental, Social and Governance (ESG) - Corporate Financial Performance (CFP) relation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to statistics from the CSRone sustainability reporting platform, there has been a dramatic increase in the number of CSR reports published in recent years, with more than half of all listed companies obtaining CSR assurance services from third parties for their CSR reports in Taiwan. The use of a third party for assurance has been shown to enhance trust in the content of reports [2][3][4], in accordance with the reputation of the organization that prepared it. Investors who are confident in the verity of disclosed CSRrelated information are more likely to regard the firm as a safe or worthy investment, and stakeholders can use this information to gain insights into the nonfinancial operations of the firm.…”
Section: Introductionmentioning
confidence: 99%